Wawasan Seni Tari Bagi Calon Pendidik Anak Usia Dini : Dance Insights for Prospective Early Childhood Educators - Depalina, Syamsiah; Kholida Nur; Annisa Wahyuni (Prodi Pendidikan Islam Anak Usia Dini Sekolah Tinggi Agama Islam Negeri Mandailing Natal- Sumatera Utara, 2021)
Law Number 14 of 2005 concerning teachers and lecturers which states that teachers and lecturers are professional positions. Professional positions are positions that require certain abilities and certain educational backgrounds. Furthermore, according to the PP of the Minister of National Education of the Republic of Indonesia No. 16 of 2007 concerning standards of academic qualifications and teacher competencies, it is said that the competencies required by teachers are divided into four categories, namely: Pedagogical Competence (Academic), Personality Competence, Social Competence (social), and Professional Competence . Early childhood education is an effort to seek and develop all the potential abilities of children from birth to the age of 6 years which in the end is the initial foundation for developing the nation, therefore educators are needed who are able to develop all the potential of early childhood. Because of their very important role, PAUD teachers are required to have high professionalism in carrying out their duties and their willingness to change for the better. One of them is mastering insight into the art of dance. The research method used is descriptive research.